There's no future, there's no hope (2023)
There's no future, there's no hope is a composition for flute, oboe, clarinet in Bb, bassoon, percussion (2 timpani and celesta), piano, violin, violoncello, contrabass and fixed audio media. The composition was inspired in the book "The Wisdom of Insecurity" by the English writer Alan Watts.